Intra-industry trade between CESEE countries and the EU15 - Ernest Dautovic; Lucia Orszaghova; Willem Schudel (European Central Bank (ECB), 2014)
The rapid increase in intra-industry trade (IIT) between the EU15 and Central, Eastern and South-Eastern European (CESEE) countries after the collapse of the Soviet Union indicates a structural change in the nature of trade in CESEE and a new process of transition and real convergence to the EU. Using a product-level trade flows database and employing linear and non-linear panel data specifications, this paper assesses the determinants of intra-industry trade between the EU15 as the main trading block and CESEE, which are further divided into the `new' EU member states (NMS) and the EU candidate countries and potential candidates (CCPC). The analysis highlights the importance of intra-industry trade in terms of achieving real convergence. The paper finds that there exist some common factors driving IIT across the sample, such as the corporate tax rate, the flexibility of exchange rate regimes and the quality of political institutions. However, the determinants of IIT between NMS and EU15 countries deviate considerably from those between CCPC and EU15 countries.
Keywords: F14; F15; F10; 330; Central and Eastern Europe; convergence criteria; economic integration; emerging Europe; EU candidate countries; horizontal IIT; intra-industry trade; panel data; real convergence; South-Eastern Europe; transition; vertical IIT; Western Balkan